Green Sukuk in Indonesia: Unraveling Legal Frameworks for Sustainable Islamic Bonds - Supriyadi, Aditya Prastian; Fidhayanti, Dwi; Ramadhita, Ramadhita; Noh, Mohd Shahid bin Mohd (El-Mashlahah, 2023)
Green sukuk is a contemporary-era sharia investment revolution that accommodates environmental aspects. Integrating Sustainable Financing in green sukuk can be an alternative investment platform contributing to sustainable development. The concept paradigm is relevant for strengthening the proportional construction of green sukuk law in Indonesia. The study aimed to analyze the concept of sustainable financing as the legal basis for implementing green sukuk in supporting sustainable development programs in Indonesia. The study used normative legal research methods. This research approach used a conceptual approach through reasoning the concepts of sustainable financing, green sukuk, and other concepts relevant to the topic of study to strengthen the discussion argument. The study showed that there are 2 (two) components of the relevance of the Sustainable Financing paradigm as the basis for implementing green sukuk in Indonesia. First, the implementation of green sukuk in various countries has rules that accommodate sustainable financing in response to climate change problems. Second, the sustainable financing Paradigm is relevant as a source of green sukuk legal construction to strengthen the policy basis for implementing environmentally sound investment in Indonesia. The urgency of the regulation is to increase investment commitments that can increase environmental resilience, alleviation of social problems and business transparency in contributing to sustainable development in Indonesia.